Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Retraction notice to “Hydrogen role in energy transition: A comparative review” [Process Saf. Environ. Prot. 184 (2024) 1069–1093] - Qusay Hassan; Sameer Algburi; Marek Jaszczur; Ali Khudhair Al-Jiboory; Tariq J. Al Musawi; Bashar Mahmood Ali; Patrik Viktor; Monika Fodor; Muhammad Ahsan; Hayder M. Salman; Aws Zuhair Sameen (Process Safety and Environmental Protection, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

Role of reactive nitrogen species in changing climate and future concerns of environmental sustainability - Muhammad Rizwan; Hurain Tanveer; Muhammad Hayder Ali; Muhammad Sanaullah; Abdul Wakeel (Environmental Science and Pollution Research, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

RETRACTED: Hydrogen role in energy transition: A comparative review - Qusay Hassan; Sameer Algburi; Marek Jaszczur; Ali Khudhair Al-Jiboory; Tariq J. Al Musawi; Bashar Mahmood Ali; Patrik Viktor; Monika Fodor; Muhammad Ahsan; Hayder M. Salman; Aws Zuhair Sameen (Process Safety and Environmental Protection, 2024)

Human biomonitoring of trace metals from different altitudinal settings of Pakistan - Syed Ali Musstjab Akber Shah Eqani; Ambreen Alamdar; Ismat Nawaz; Syed Sayyam Abbas Shah; Tasawar Khanam; Qurat Ul Ain Hayder; Muhammad Sohail; Ioannis A. Katsoyiannis; Heqing Shen (Environmental Science and Pollution Research, 2024)

Effect of crop combination on yield performance, nutrient uptake, and land use advantage of cereal/legume intercropping systems - Muhammad Ali Raza; Wang Zhiqi; Hassan Shehryar Yasin; Hina Gul; Ruijun Qin; Sana Ur Rehman; Aqib Mahmood; Zafar Iqbal; Zaheer Ahmed; Shuanglong Luo; Chen Juan; Xue Liang; et al. (Field Crops Research, 2023)

A bacterial consortium and L-tryptophan boosted glyphosate removal, mungbean growth and physiology in contaminated soil - Qammar Farooq; Muhammad Imran Khan; Muhammad Hayder Ali; Safdar Bashir; Muhammad Azam; Rashad Qadri; Basharat Ali; Muhammad Dawood; Muhammad Iftikhar Hussain (Arabian Journal of Geosciences, 2023)

Retraction Note: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2023)

Commiphora myrrh: a phytochemical and pharmacological update - Gaber El-Saber Batiha; Lamiaa Wasef; John Oluwafemi Teibo; Hazem M. Shaheen; Ali Muhammad Zakariya; Opeyemi Abigail Akinfe; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbee; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Medicinal plants have a long track record of use in history, and one of them is Commiphora myrrh which is commonly found in the southern part of Arabia, the northeastern part of Africa, in Somalia, and Kenya. Relevant literatures were accessed via Google Scholar, PubMed, Scopus, and Web of Science to give updated information on the phytochemical constituents and pharmacological action of Commiphora myrrh . It has been used traditionally for treating wounds, mouth ulcers, aches, fractures, stomach disorders, microbial infections, and inflammatory diseases. It is used as an antiseptic, astringent, anthelmintic, carminative, emmenagogue, and as an expectorant. Phytochemical studies have shown that it contains terpenoids (monoterpenoids, sesquiterpenoids, and volatile/essential oil), diterpenoids, triterpenoids, and steroids. Its essential oil has applications in cosmetics, aromatherapy, and perfumery. Research has shown that it exerts various biological activities such as anti-inflammatory, antioxidant, anti-microbial, neuroprotective, anti-diabetic, anti-cancer, analgesic, anti-parasitic, and recently, it was found to work against respiratory infections like COVID-19. With the advancement in drug development, hopefully, its rich phytochemical components can be explored for drug development as an insecticide due to its great anti-parasitic activity. Also, its interactions with drugs can be fully elucidated. This review highlights an updated information on the history, distribution, traditional uses, phytochemical components, pharmacology, and various biological activities of Commiphora myrrh . Graphical abstract Graphical summary of the phytochemical and pharmacological update of Commiphora myrrh

RETRACTED ARTICLE: Detection of HPV16 viral load in L2 gene as a related predictor of cervical cancer among women in Dhi-Qar province by qRT-PCR - Abduladheem Turki Jalil; Muhammad Usman Faryad Khan; Hayder Ali Muhammed; Ahmed Abdulhussein Kawen; Balsam Qubais Saeed; Aleksandr Karevskiy (Molecular Biology Reports, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Combined application of Bacillus sp. MN-54 and phosphorus improved growth and reduced lead uptake by maize in the lead-contaminated soil - Muhammad Junaid Afzal; Muhammad Imran Khan; Sardar Alam Cheema; Saddam Hussain; Muhammad Anwar-ul-Haq; Muhammad Hayder Ali; Muhammad Naveed (Environmental Science and Pollution Research, 2020)